2021
DOI: 10.1101/2021.11.08.467746
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of function of bHLH transcription factor Nrd1 in tomato induces an arabinogalactan protein-encoding gene and enhances resistance toPseudomonas syringaepv.tomato

Abstract: Basic helix-loop-helix (bHLH) transcription factors constitute a superfamily in eukaryotes but their roles in plant immunity remain largely uncharacterized. We found that the transcript abundance in tomato leaves of one bHLH transcription factor-encoding gene, Nrd1 (negative regulator of resistance to DC3000 1), was significantly increased after treatment with the immunity-inducing flgII-28 peptide. Plants carrying a loss-of-function mutation in Nrd1 (Λnrd1) showed enhanced resistance to Pseudomonas syringae p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 99 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…Moreover, there were other TFs with genes that were downregulated, WRKY (four genes), NAC domain (three genes), bHLH (two genes), bZIP (four genes), and ERF (two genes) (Table S6). Although TFs constitute a large family of proteins and the functional role of many of them is yet to be characterized, some of the earlier studies on TFs have demonstrated both the positive and negative roles in the plant immunity response [67]- [69]. For instance, NAC is one of the well-studied TFs and they were confirmed as both positive and negative regulators of defense-related genes [70].…”
Section: Mitogen-activated Protein Kinase (Mapk) Signaling In Respons...mentioning
confidence: 99%
“…Moreover, there were other TFs with genes that were downregulated, WRKY (four genes), NAC domain (three genes), bHLH (two genes), bZIP (four genes), and ERF (two genes) (Table S6). Although TFs constitute a large family of proteins and the functional role of many of them is yet to be characterized, some of the earlier studies on TFs have demonstrated both the positive and negative roles in the plant immunity response [67]- [69]. For instance, NAC is one of the well-studied TFs and they were confirmed as both positive and negative regulators of defense-related genes [70].…”
Section: Mitogen-activated Protein Kinase (Mapk) Signaling In Respons...mentioning
confidence: 99%